Oblicz wartość wyrażenia (rozpisz): ([latex] sqrt{6 frac{1}{4} } [/latex]-3[latex] frac{1}{2} [/latex])*[latex] sqrt[3]{27} [/latex]:[latex] sqrt{25} [/latex] Prosze wejdźcie bo to jest dobrze zapisane.

Oblicz wartość wyrażenia (rozpisz): ([latex] sqrt{6 frac{1}{4} } [/latex]-3[latex] frac{1}{2} [/latex])*[latex] sqrt[3]{27} [/latex]:[latex] sqrt{25} [/latex] Prosze wejdźcie bo to jest dobrze zapisane.
Odpowiedź

[latex]( sqrt{} frac{25}{4} - frac{7}{2} )*3:5= (frac{5}{2} - frac{7}{2} )*3:5=-1*3:5=-3:5=-0,6 \ sqrt[3]{27} =3 \ sqrt{25} =5[/latex]

Dodaj swoją odpowiedź